Dynamics of Lady’s slipper orchid (Cypripedium calceolus L.) population at Lake Kwiecko (West Pomerania) - Korczyński, Maciej; Krasicka-Korczyńska, Ewa (Biodiversity: Research and Conservation, 2015)
Cypripedium calceolus is considered an endangered species in the territory of Poland. Population of this rare species, situated at Lake Kwiecko (Western Pomerania), was regularly monitored in the years 1986-2013. The studied population has been under the permanent influence of the nearby hydroelectric power plant for almost 45 years. The field observations showed that the power plant had no negative impact on the condition of Cypripedium calceolus population. An indication of its good condition was, among others, an increase in the size - from 150 to 350 specimens within the study period.